Vestibular Aqueduct Size Correlates With the Degree of Cochlear Hydrops in Patients With and Without Menière's Disease. Issue 10 (December 2021) - Grosser, Desiree; Willenborg, Kerstin; Dellani, Paulo; Avallone, Emilio; Götz, Friedrich; Böthig, Dietmar; Warnecke, Athanasia; Lanfermann, Heinrich; Lenarz, Thomas; Giesemann, Anja
Abstract : Objective: To correlate the CT imaging findings of the visibility and size of the vestibular aqueduct (VA) with the degree of the cochlear hydrops determined in MRI late imaging of the hydrops. Study Design: Retrospective study. Setting: Tertiary referral center. Patients: A total of 127 patients (62 women, 65 men, average age 55.6 yrs): 86 of these were diagnosed with Menière's disease (American Academy of Otolaryngology–Head and Neck Surgery [AAO-HNS] criteria; 67 unilateral, 19 bilateral). Intervention(s): Temporal bone CT and hydrops MRI were performed in all patients. Main Outcome Measure(s): Visibility/width of the VA in temporal bone CT and grade of cochlear hydrops evaluated by MRI. Results: The width of the VA is significantly smaller in patients diagnosed with Menière's disease (30% non-visible VA), compared with the patients who did not fulfill the diagnostic criteria of Menière's disease (12% non-visible VA) (double sided Spearman correlation, p  < 0.001). In all ears of patients diagnosed with Menière's disease the width of the VA was significantly correlated with the degree of the cochlear hydrops (in cases of non-visible VA 65% [34/52] ears presented with hydrops grade 3 or 4; 13% [7/52] ears presented with hydrops grade 1 or 2 and 21% [11/52] ears showed no hydrops) (Spearman correlation p  = 0.001/ p  < 0.01). This is also true for all ears that can be summarized as hydrophic ear disease (symptomatic ears that present with a hydrops in MRI). Conclusions: The results of our study could confirm the importance of the VA in the pathogenesis of the endolymphatic hydrops in vivo.